A comparative correlational study of coping strategies and quality of life in patients with chronic heart failure and the general Swedish population. Issue 3 (18th April 2017) - Nilsson, Annika; Carlsson, Marianne; Lindqvist, Ragny; Kristofferzon, Marja‐Leena
Abstract: Aim: The aim was to compare coping strategies and quality of life (QoL) in patients with chronic heart failure (CHF) with such strategies and QOL in persons from two general Swedish populations and to investigate relationships between personal characteristics and coping strategies. Design: A cross‐sectional, comparative and correlational design was used to examine data from three sources. Methods: The patient group ( n  =   124), defined using ICD‐10, was selected consecutively from two hospitals in central Sweden. The population group ( n  =   515) consisted of persons drawn randomly from the Swedish population. Data were collected with questionnaires in 2011; regarding QoL, Swedish population reference data from 1994 were used. Results: Overall, women used more coping strategies than men did. Compared with the general population data from SF‐36, patients with CHF rated lower QoL. In the regression models, perceived low "efficiency in managing psychological aspects of daily life" increased use of coping. Other personal characteristics related to increased use of coping strategies were higher education, lower age and unsatisfactory economic situation.